An Anthropomorphic Musculoskeletal System with Soft Joint and Multifilament Pneumatic Artificial Muscles - Zhonghan Lin; Qi Shao; Xin-Jun Liu; Huichan Zhao (Advanced Intelligent Systems, 2022)
Robotic manipulators are expected to enhance humans’ ability to grasp and manipulate objects. Soft materials offer innovative opportunities to develop robotic manipulators that are inherently compliant, physically robust, and interact safely with humans. Herein, a soft‐material‐based musculoskeletal module is reported. Inspired by the human shoulder complex, a lightweight and compact three‐degree‐of‐freedom (three‐DOF) membrane‐covered passive joint with a large range of motion (>180°) in all DOFs, small rotational resistance (<0.2 Nm), and large axial load‐bearing capacity (>80 N) benefiting from the hydrostatic stress of its filled liquid is developed. To actuate the joint, a helical‐structured pneumatic artificial muscle fiber (HPAMF) with a high energy density of 36 J kg−1 is designed. Moreover, it is investigated how to eliminate the Mullins effect of fibers made from silicone rubber to increase the repeatability and consistency between fibers and ensure the musculoskeletal system achieves stable motion by overcoming the snap‐through instability. Finally, the musculoskeletal system achieves open‐loop controlled three‐DOF motion with load‐bearing capacity in a compact space via pre‐stretching and antagonistic arrangement of 60 HPAMFs as 12 independent bundles. It is believed that the proposed musculoskeletal module can be assembled and developed as a soft manipulator to assist people in their activities of daily living.